2013
DOI: 10.31129/lumat.v1i3.1104
|View full text |Cite
|
Sign up to set email alerts
|

Early Mathematical Performance in Finnish Kindergarten and Grade One

Abstract: The present study assessed Finnish kindergarten (N = 177, Mage = 76.4 months, SD = 3.7 months) and grade one (N = 178, Mage = 87.2 months, SD = 3.7 months) children's mathematical skills in the beginning of the school year. The mathematical skills were assessed once using researcher-developed paper-pencil tests. The variance analysis (ANOVA) was used to study the effects of age and gender on performance level. Boys and girls performed similarly in both samples, but age effects were found in the kindergarten an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…This process showed that mathematics program and education practices should be structured on a sound basis by taking into account both mathematical content areas and the developmental characteristics of children. Considering that pedagogical approaches supporting the development of mathematical skills are seen as effective in enhancing these skills in children (Mononen & Aunio, 2013); the importance of teachers' pedagogical content knowledge related to mathematics has become prominent (Gifford, 2005). Pedagogical content knowledge in education was originally proposed by Shulman (1986), and encompasses knowing what to teach according to age groups and integrating that with the knowledge of how to teach it.…”
Section: Introductionmentioning
confidence: 99%
“…This process showed that mathematics program and education practices should be structured on a sound basis by taking into account both mathematical content areas and the developmental characteristics of children. Considering that pedagogical approaches supporting the development of mathematical skills are seen as effective in enhancing these skills in children (Mononen & Aunio, 2013); the importance of teachers' pedagogical content knowledge related to mathematics has become prominent (Gifford, 2005). Pedagogical content knowledge in education was originally proposed by Shulman (1986), and encompasses knowing what to teach according to age groups and integrating that with the knowledge of how to teach it.…”
Section: Introductionmentioning
confidence: 99%